Anticoagulation Management and Antithrombin Supplementation Practice during Veno-venous Extracorporeal Membrane Oxygenation: A Worldwide Survey. (March 2020) - Protti, Alessandro; Iapichino, Giacomo E.; Di Nardo, Matteo; Panigada, Mauro; Gattinoni, Luciano
Abstract : Background: There is a lack of consensus on how to manage anticoagulation during veno-venous extracorporeal membrane oxygenation, including antithrombin monitoring and supplementation. The authors' aim was to determine current practice in a large number of extracorporeal membrane oxygenation centers around the world. Methods: This was an electronic survey disseminated in 2018 to directors and coordinators of extracorporeal membrane oxygenation centers as well as to extracorporeal membrane oxygenation experts. Participating centers were classified according to some covariates that may affect practice, including 2017 gross national income per capita, primary patient population, and annual extracorporeal membrane oxygenation patient volume. Results: The authors analyzed 273 unique responses from 50 countries. Systemic anticoagulation was routinely prescribed in 264 (96.7%) centers, with unfractionated heparin being the drug of choice in 255 (96.6%) of them. The preferred method to monitor anticoagulation was activated partial thromboplastin time in 114 (41.8%) centers, activated clotting time in 82 (30.0%) centers, and anti-factor Xa activity in 62 (22.7%) centers. Circulating antithrombin activity was routinely monitored in 133 (48.7%) centers. Antithrombin supplementation was routinely prescribed in 104 (38.1%) centers. At multivariable analyzes, routine antithrombin supplementation was associated with national income, being less likely in lower- than in higher-income countries (odds ratio, 0.099 [95% CI, 0.022 to 0.45]; P = 0.003); with primary patient population being more frequent in mixed (odds ratio, 2.73 [1.23 to 6.0]; P = 0.013) and pediatric-only centers (odds ratio, 6.3 [2.98 to 13.2]; P < 0.001) than in adult-only centers; but not with annual volume of extracorporeal membrane oxygenation cases, being similarly common in smaller and larger centers (odds ratio, 1.00 [0.48 to 2.08]; P = 0.997). Conclusions: There is large practice variation among institutions regarding anticoagulation management and antithrombin supplementation during veno-venous extracorporeal membrane oxygenation. The paucity of prospective studies and differences across institutions based on national income and primary patient population may contribute to these findings. Abstract : Based on 273 responses from 50 countries, unfractionated heparin is used in 96.6% of centers, with partial thromboplastin time monitoring in 41.8%, activated clotting time in 30.0%, and anti-factor Xa activity in 22.7% of centers. Antithrombin is monitored in 48.7% of centers and actively repleted in 38.1% of centers, mainly in high-income regions and in pediatric patients.Supplemental Digital Content is available in the text.